Ergothioneine improves healthspan of aged animals by enhancing cGPDH activity through CSE-dependent persulfidation: short article - Petrovic, Dunja; Slade, Luke; Paikopoulos, Yiorgos; D’Andrea, Davide; Savic, Nevena; Stancic, Ana; Miljkovic, Jan Lj; Vignane, Thibaut; Drekolia, Maria-Kyriaki; Mladenovic, Dusan; Sutulovic, Nikola; Refeyton, Alice; et al. (Cell metabolism, 2025)
Ergothioneine (ET), a dietary thione/thiol, is receiving growing attention for its possible benefits in healthy aging and metabolic resilience. Our study investigates ET’s effects on healthspan in aged animals, revealing lifespan extension and enhanced mobility in Caenorhabditis elegans, accompanied by improved stress resistance and reduced age-associated biomarkers. In aged rats, ET administration enhances exercise endurance, muscle mass, and vascularization, concomitant with higher NAD+ levels in muscle. Mechanistically, ET acts as an alternative substrate for cystathionine gamma-lyase (CSE), stimulating H2S production, which increases protein persulfidation of more than 300 protein targets. Among these, protein-persulfidation-driven activation of cytosolic glycerol-3-phosphate dehydrogenase (cGPDH) primarily contributes to the ET-induced NAD+ increase. ET’s effects are abolished in models lacking CSE or cGPDH, highlighting the essential role of H2S signaling and protein persulfidation. These findings elucidate ET’s multifaceted actions and provide insights into its therapeutic potential for combating age-related muscle decline and metabolic perturbations.
Online verfügbar: 21. Januar 2025, Artikelversion: 4. Februar 2025
Gesehen am 17.07.2025